ANALYSIS OF FACTORS AFFECTING THE NUMBER OF POOR PEOPLE IN DISTRICTS/CITIES IN BALI PROVINCE - I Gusti Ayu Oka Candra Kartika; Putu Ayu Pramitha Purwanti (Adisam Publisher, 2025)
Poverty is one of the most complex social issues and continues to be a major challenge for Indonesia. The complexity of poverty stems not only from low income and consumption levels but also from various interrelated factors such as unequal access to education, healthcare, and employment—especially in rural and remote areas. This study fills a gap in the literature by integrating five important factors within the local context of Bali Province, which have rarely been explored in previous research, particularly considering the post-pandemic economic conditions and regional development disparities. The research was conducted across 8 regencies and 1 city in Bali Province, aiming to analyze the influence of variables including tourism sector contribution, Human Development Index (HDI), working-age population, labor force participation rate (LFPR), and household consumption level on the number of poor people. A multiple linear regression method was applied, using 54 observations. The findings show that: (1) the variables of tourism sector contribution, HDI, working-age population, labor force participation rate, and household consumption level have a simultaneous and significant effect on poverty levels in the districts/cities of Bali Province from 2019 to 2024; (2) the variables of tourism sector contribution and household consumption level have a partially negative and significant effect on poverty; (3) the HDI variable has a partially positive and significant effect on poverty; and (4) the working-age population and labor force participation rate variables have a partially negative but not significant effect on poverty.